The Evolution of Deprivation of Liberty Penalties in Peru. An Overview of Inca Punishment, Colonial Prisons, and Penitentiary Administration in the Republic Era - Vega Santa Gadea, Fernando (1973)
An in-depth exploration of punishment throughout Peruvian history serves as a crucial foundation for understanding and potentially enhancing the prison system. This article aims to scrutinize the historical trajectory of custodial sentencing in Peru. Leveraging accounts from chroniclers, compilations of the Laws of the Indies, and historical studies, the analysis unfolds across three distinct historical periods: the Inca justice system, colonial-era prisons, and challenges encountered during the Republic Era. Through this examination, the article seeks to elucidate any significant shifts within the prison system across these epochs. Finally, it provides insights into the primary factors contributing to the shortcomings of the penitentiary system.